БУКТРЕЙЛЕР ЯК ЗАСІБ ПІДВИЩЕННЯ ЧИТАЦЬКОЇ АКТИВНОСТІ МАЙБУТНІХ УЧИТЕЛІВ ПОЧАТКОВОЇ ШКОЛИ У НАВЧАННІ ДИТЯЧОЇ ЛІТЕРАТУРИ - Vardanian, Maryna V. (Information technologies and learning tools, 2018)
The article deals with the problem of reducing reader activity and ways of its solving. The paper represents the possibilities of using ICT while teaching "Children's Literature" course for the specialty "Primary Education" in the higher education institutions. The publishing and library booktrailers are analyzed. This research shows the concept of education booktrailer, its main tasks and methods of implementing as the information and cognitive technology. Moreover it defines the stages of work on the booktrailer such as organization, preparation, implementation and presentation. The education booktrailer is considered to be one of the effective means for increasing reader activity among future primary school teachers. It influences greatly the formation of literature and ICT competencies. This article provides the samples of booktrailers done by students since 2013. В статье поднимается проблема снижения читательской активности и пути ее решения. Исследованы возможности применения ИКТ при преподавании курса «Детская литература» в высшей школе на примере специальности «Начальное образование». Проанализированы издательский и библиотечный буктрейлер. Введено понятие образовательного буктрейлера как информационно-когнитивной технологии. Рассмотрены основные задачи образовательного буктрейлера, методику его использования. Определены этапы работы над буктрейлер: организационный, подготовительный, этап реализации и презентации. Образовательный буктрейлер рассмотрен как одно из эффективных средств повышения читательской активности будущих педагогов начальной школы, влияющее на формирование литературоведческих и ИКТ-компетентностей. Приведены примеры буктрейлеров, созданных студентами, начиная с 2013 года. У статті порушується проблема зниження читацької активності і шляхи її вирішення. Досліджено можливості застосування ІКТ під час викладання курсу «Дитяча література» у вищій школі на прикладі спеціальності «Початкова освіта». Проаналізовано видавничий і бібліотечний буктрейлер. Уведено поняття освітнього буктрейлера як інформаційно-когнітивної технології. Розглянуто основні завдання освітнього буктрейлера, методику його виконання. Визначено етапи роботи над буктрейлером: організаційний, підготовчий, етап реалізації та презентації. Освітній буктрейлер розглянуто як один з ефективних засобів підвищення читацької активності майбутніх педагогів початкової школи, що впливає на формування літературознавчих та ІКТ-компетентностей. Наведено приклади буктрейлерів, що виконані студентами з 2013 року.